Perception of Peru and Peruvian Citizens in a Sample of Chilean College Students - Zambrano-Mora, Alfredo (2017)
We examined and compared perceptions Chilean college students have of the Peruvian and their own society. To this end, we studied a sample of 453 students (247 males, and 206 females, ages between 16 and 48). Two scales were used, one evaluated Peruvian and Chilean societies and the second scale was subdivided into three components (You,A Chilean like you, A Peruvian like you) to evaluate common traits (ambitious, responsible, tenacious, and intelligent). Results indicate that the perception of the sample revealed that Chilean society was more modern, democratic, and close to First World standards than the Peruvian. Levels of poverty and corruption were perceived as similar. Finally, Chileans were considered more competitive, whereas Peruvian more entrepreneurial.